A congestion avoidance game for information exchange on intersections in heterogeneous vehicular networks. (1st May 2017) - Chen, Chen; Qiu, Tie; Hu, Jinna; Ren, Zhiyuan; Zhou, Yang; Sangaiah, Arun Kumar
Abstract: Recently, the concept of HetVNET (Heterogeneous Vehicular NETwork) is greatly motivated by the fact that present wireless networks not only offers their attractive benefits, but also bring their shortcomings together. In this paper, by integrating the GIS (Geographic Information System), GPS (Global Position System), Sensor network, Vehicular Ad Hoc Networks (VANETs) and other localization technologies into our work, we propose a RoS (Requirement of Safety) aware services scheduling in the HetVNET to improve the packets delivery ratio, increase the spectral efficiency and alleviate the packet congestion as well. In addition, through utilizing the SINR-based (Signal to Interference plus Noise Ratio) utility and social optima searching strategy, our proposed algorithm outperforms the IEEE 802.11p in terms of the throughput as well as service miss ratio with the EDF (Earliest Deadline First) queuing mechanism. In addition, to reflect the increased transmission opportunities, the channel busy ratio under different configurations is also compared with a previous work DynB (Dynamic Beaconing).